2019
DOI: 10.1111/jep.13324
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different venous thromboembolism risk assessment machine learning models in Chinese patients

Abstract: Objective: Venous thromboembolism (VTE) is a fatal complication and the most common preventable cause of death in hospitals. The risk-to-benefit ratio of thromboprophylaxis depends on the performance of the risk assessment model. A linear model, the Padua model, is recommended for medical inpatients in the United States but is not suitable for Chinese inpatients due to differences in race and disease spectrum. Currently, machine learning (ML) methods show advantages in modeling complex data patterns and have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Some feature types are more informative than others: quantitative features contain more details than the ordinal ones, and the same relationship holds between ordinal and categorical features. The empirical impact of this statement is present in many of the papers included in this review: risk scores obtained by reducing the number of used features often end up using more quantitative and ordinal features than categorical ones [14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Features Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some feature types are more informative than others: quantitative features contain more details than the ordinal ones, and the same relationship holds between ordinal and categorical features. The empirical impact of this statement is present in many of the papers included in this review: risk scores obtained by reducing the number of used features often end up using more quantitative and ordinal features than categorical ones [14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Features Typesmentioning
confidence: 99%
“…Our literature review found that RF appeared second highest in the papers we reviewed, ranging from classification tasks 26,33,46 to regression tasks. Many authors use RFs to predict all-cause mortality, and others apply RF to particular cardiovascular diseases 37,46 or for risk assessment of heart failure 33 and venous thromboembolism 22 . In some studies, authors claim that the inferred RF models are helpful for clinical decisions, allowing to estimate whether a patient is suffering from heart failure with preserved ejection fraction or not 33 , and that their risk score assessment performs better than the state-of-the-art ones.…”
Section: Random Forestmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on artificial intelligence in other medical scenarios are exponentially increasing in the literature. In patients with VTE, ML methods have been used for DVT diagnosis, 14 PE diagnosis, 16 risk stratification of acutely ill medical patients, 18,15 and in the prediction of VTE after surgery 17 or post-hospitalization 13 . Overall, supervised ML modestly improved the performance of LR, with some exceptions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, Wang et al reported on the performance of nine ML methods to predict VTE in hospitalized patients in a single center study. 15 In the validation subgroup, the difference in the c-statistics of the best performing method (Random…”
Section: Accepted Manuscriptmentioning
confidence: 99%